Some remarks on evaluating the quality of the multiple sequence alignment based on the BAliBASE benchmark - Błażewicz, Jacek; Formanowicz, Piotr; Wojciechowski, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
BAliBASE is one of the most widely used benchmarks for multiple sequence alignment programs. The accuracy of alignment methods is measured by bali score - an application provided together with the database. The standard accuracy measures are the Sum of Pairs (SP) and the Total Column (TC). We have found that, for non-core block columns, results calculated by bali score are different from those obtained on the basis of the formal definitions of the measures.
Keywords: multiple sequence alignment; reference alignment; alignment accuracy